Bahasa Inggris - Miftahul Hasanatun Alfiah; Bramastia; Sukarmin (Postgraduate, University of Mataram, 2025)
Technological advancements have significantly impacted the environment, highlighting the need to improve scientific literacy to address these effects. However, PISA data indicates that Indonesian students' scientific literacy remains low. This study aims to analyze the effectiveness of Project-Based Learning (PjBL) in enhancing scientific literacy among secondary school students through a literature review method. PjBL fosters active engagement, collaboration, and critical thinking by involving students in meaningful projects. The findings demonstrate that PjBL improves scientific literacy and creativity, though its implementation faces challenges such as limited resources, time constraints, and insufficient teacher training. The study concludes that PjBL is a promising approach to improving scientific literacy in Indonesia, provided adequate teacher training and resources are available to support its implementation.